A retrospective study on paediatric dental treatment under general anaesthesia at a tertiary public facility in Australia. Issue 3 (December 2020) - Zhou, Xiaoyan; Nanayakkara, Shanika; Songsiripradubboon, Siriporn; Gao, Jinlong; Prabhu, Neeta
Abstract: Background: This study aimed to evaluate the clinical profile of children referred for dental treatment under general anaesthesia (DGA) at a tertiary public facility in Australia in 2016. Materials and methods: Patients (n = 315, age range 1.33–15.75 years) who received DGA in 2016 were included. Demographic and clinical information was extracted from the dental records and analysed using descriptive analysis methods and independent samples t -test. Results: Among the patients (188 males, 127 females) included in this study, majority were from suburbs with relatively low socio-economic status and under 6 years of age (62.54%). 69.84% were placed as low priority on the waiting list (average waiting time 298.61 days), with 13.01% of patients re-presenting with dental emergencies during the waiting time. Caries was the major indication for DGA and extraction was the most common treatment in all age groups (<6-year group-40%, 6-12-year group-38% and >12-year group-36%). Stainless steel crown was the second common treatment in <6-year group (27%). On average, a child received dental treatment on approximately ten teeth and the average procedure time was 66.88 ± 23.54 min. Conclusion: Despite existing caries prevention programs, dental caries is the major indicator for DGA in the paediatric population. This study emphasises the importance of early preventive care particularly targeting higher-caries-risk children to minimise the need of DGA.